ChemInform Abstract: Synthesis of Highly Substituted N‐Hydroxy Piperidine via Intramolecular Reductive Cyclization of 1‐Keto‐5‐ketoxime. Issue 29 (1st July 2013) - Nagaraj, Muthupandi; Boominathan, Muthusamy; Manikannan, Ramaiyan; Muthusubramanian, Shanmugam; Bhuvanesh, Nattamai
Abstract: Title compounds (III) are synthesized each as racemate of a single diastereomer.